2019
DOI: 10.1111/jai.13868
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of reproductive biology of curimba Prochilodus lacustris (Pisces, Prochilodontidae) in a tropical lake in Northeastern Brazil

Abstract: This study evaluated the annual cycle of biological reproductive aspects of Prochilodus lacustris, a neotropical fish species, in Baixada Maranhense Protection Area in northeastern Brazil. Fish were collected monthly between June of 2015 and June of 2016 using gill nets. In the laboratory, 600 individuals were weighed, measured, and eviscerated to obtain biometric data and data for the microscopic and macroscopic analyses of the maturation stages of the gonads. These analyses allowed the determination of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The high values of GSI and low condition factor were recorded in the month of June which indicated that there exists no relation between GSI and condition factor. The present finding is in corroboration with Cardoso et al (2019) who reported the reverse pattern for mean condition factor and GSI in Prochilodus lacustris. The condition factor relatively depended upon a number of factors such as environmental conditions and ecological parameters, seasons, food availability, gonadal development, fishing pressures and stress conditions (Zargar et al, 2012;Ahmad, 2013;Ali et al, 2014, Komsari et al, 2015.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The high values of GSI and low condition factor were recorded in the month of June which indicated that there exists no relation between GSI and condition factor. The present finding is in corroboration with Cardoso et al (2019) who reported the reverse pattern for mean condition factor and GSI in Prochilodus lacustris. The condition factor relatively depended upon a number of factors such as environmental conditions and ecological parameters, seasons, food availability, gonadal development, fishing pressures and stress conditions (Zargar et al, 2012;Ahmad, 2013;Ali et al, 2014, Komsari et al, 2015.…”
Section: Discussionsupporting
confidence: 93%
“…reported by Abujam and Biswas (2011) and Kashyap et al (2016). However, it is worth mentioning here that several other workers (Qayyum and Qasim, 1964;Cardoso et al 2019) recorded the dominance of females over males. In the present study, male and female sex ratio was 1:0.93 which did not differ significantly from the hypothetical sex ratio of 1:1.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation